Glycolytic flux sustains human Th1 identity and effector function via STAT1 glycosylation - Abir, Ariful Haque; Benz, Julia; Frey, Benjamin; Bruns, Heiko; Krönke, Gerhard; Gaipl, Udo; Schober, Kilian; Mougiakakos, Dimitrios; Mielenz, Dirk (Life Science Alliance, 2026)
T helper (Th) cell lineages are linked to metabolism, but precise mechanisms in human Th1 cells remain unclear. We addressed this question by in vitro stimulation and CRISPR/Cas9-mediated gene editing. Metabolic profiling revealed enhanced glycolytic activity in Th1 versus non-polarized cells, evidenced by increased extracellular acidification rate, ATP production via glycolysis, lactate secretion, NADH abundance, and elevated glycolysis-dependent anabolic activity. Inhibition of glycolysis reduced IFNγ production and STAT1 phosphorylation independent of JAK1/2 or SHP2 activity and STAT1 abundance, implicating glycolysis directly in sustaining STAT1-mediated Th1 functionality. O-glycosylation of STAT1 via O-glycosyltransferase was pivotal in modulating STAT1 activity. Pharmaceutical O-glycosyltransfer-ase inhibition prevented Th1 differentiation as well as STAT1 O-glycosylation. CRISPR/Cas9 mediated mutation of the O-glycosylation Ser499 and Thr510 sites diminished STAT1 Ser727 phosphorylation and IFNγ synthesis. Together, this study highlights glycolysis as key regulator of human Th1 cell identity and effector function, with STAT1 O-glycosylation selectively maintaining Th1 effector capacity. This mechanism could be explored to safeguard Th1 cells.
CRIS-Team Scopus Importer:2025-11-21